Latissimus dorsi flap with vascularized lymph node transfer for lymphedema treatment: Technique, outcomes, indications and review of literature. Issue 1 (12th December 2016) - Inbal, Amir; Teven, Chad M.; Chang, David W.
Abstract : Background and Objectives: One of the surgical treatment options for lymphedema is vascularized lymph node transfer (VLNT). We present our experience with latissimus dorsi (LD) flap based VLNT for lymphedema treatment. Methods: We reviewed 14 consecutive patients treated with pedicled or free LD VLNT between 2014 and 2016 for recalcitrant upper or lower extremity lymphedema. Seven patients underwent lymphovenous bypass in addition to LD VLNT. Limb volume and quality of life scores using the Lymphedema Life Impact Scale (LLIS) were analyzed for quantitative and qualitative assessment. Results: Mean duration of lymphedema was 69 months (range 24–124 months). Follow‐up ranged from 3 to 12 months (mean 6.7 month). Major complications included one free flap loss and one reoperation for thrombosis. Mean preoperative volume differential between normal and affected limb was 35% (range 3–87%). Volume differential reduction was 48%, 28%, and 46% at 3, 6, and 12 months, respectively. The LLIS score improved from mean of 46.8 before surgery to a mean of 38.6 at 12 month, demonstrating improvement in quality of life. Conclusions: The LD VLNT provides a viable option for treatment of UE and LE lymphedema in selected patients. J. Surg. Oncol. 2017;115:72–77 . © 2016 Wiley Periodicals, Inc.